2013
DOI: 10.1002/ps.3619
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing supercooling capacity of the koinobiont endoparasitoid Venturia canescens (Hymenoptera: Ichneumonidae)

Abstract: Adults of V. canescens displayed an enhanced ability to supercool, however, they appear to be less cold tolerant than their respective hosts. This information would be useful in determining the potential of using V. canescens as a biological agent in Integrated Pest Management (IPM) programs, taking into consideration the adverse effects of low temperatures on its survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(33 reference statements)
2
10
0
Order By: Relevance
“…This direct response to non-suitable environmental conditions, and the subsequent response with the return of the favorable conditions, i.e. increase of temperature and host availability, may mostly suggest quiescence rather than diapause [8,38,39]. Andreadis et al [39] found that the parasitoid was generally more susceptible than the host while following a similar protocol with low temperature or the exposure of the endoparasitoid Venturia canescens (Gravenhorst) (Hymenoptera: Ichneumonidae) on larvae of the Mediterranean flour moth, Ephestia kuehniella Zeller (Lepipdoptera: Pyralidae).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This direct response to non-suitable environmental conditions, and the subsequent response with the return of the favorable conditions, i.e. increase of temperature and host availability, may mostly suggest quiescence rather than diapause [8,38,39]. Andreadis et al [39] found that the parasitoid was generally more susceptible than the host while following a similar protocol with low temperature or the exposure of the endoparasitoid Venturia canescens (Gravenhorst) (Hymenoptera: Ichneumonidae) on larvae of the Mediterranean flour moth, Ephestia kuehniella Zeller (Lepipdoptera: Pyralidae).…”
Section: Discussionmentioning
confidence: 99%
“…However, Cagnotti et al [38] reported that Trichogramma nerudai Pintureau (Hymenoptera: Trichogrammatidae) prepupae, that had been stored at suboptimal temperature were not affected when the storage was 10 or 20d. In this context, preconditioning may play a positive role [38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major ways organisms protect themselves from sudden changes in their environment is through the phenotypic plasticity of physiological performance and tolerance of extremes [62]. Acclimation to low temperatures can improve the supercooling ability of insects [63,64]. Additionally, changes in the SCP with treatment or season can indicate biochemical or physiological changes, which may help increase survival [65].…”
Section: Discussionmentioning
confidence: 99%
“…For the larval endoparasitoid Venturia canescens (Gravenhorst) (Hymenoptera: Ichneumonidae), Eliopoulos et al [ 47 ] noted that there was a critical egg maturation stage, which was directly related with viability and progeny production capacity. For the same species, Andreadis et al [ 48 ] found that cold tolerance was negatively correlated with parasitoid age. We are unaware if egg exposure to low temperatures increases their suitability for parasitism, in the same way that larval irradiation positively affects parasitism in moth larvae by H .…”
Section: Discussionmentioning
confidence: 99%